Odpowiedź :
a) {y=6x+26
5x=7y+3
y = 6x + 26
5x = 7 (6x + 26) + 3
y = 6x + 26
5x = 42x + 182 + 3
y = 6x + 26
5x - 42 x = 185
y = 6x + 26
-37x = 185 | ( : -37)
y = 6x + 26
x= -5
y = 6 * (-5) + 26
x = -5
y= -30 + 26
x = -5
y= -4
x= -5
5x=7y+3
y = 6x + 26
5x = 7 (6x + 26) + 3
y = 6x + 26
5x = 42x + 182 + 3
y = 6x + 26
5x - 42 x = 185
y = 6x + 26
-37x = 185 | ( : -37)
y = 6x + 26
x= -5
y = 6 * (-5) + 26
x = -5
y= -30 + 26
x = -5
y= -4
x= -5
A.
a)
y=6x +26
5x=7y+3
y=6x+26
5x=7(6x+26)+3
y=6x+26
5x=42x+182+3
y=6x+26
5x-42x=185
y=6x+26
-39x=185 /-39
y=6x+26
x=-5
y=6(-5)+26
x=-5
y=-4
x=-5
b) Co tam jest przy tej 2 ??
c)
a)
y=6x +26
5x=7y+3
y=6x+26
5x=7(6x+26)+3
y=6x+26
5x=42x+182+3
y=6x+26
5x-42x=185
y=6x+26
-39x=185 /-39
y=6x+26
x=-5
y=6(-5)+26
x=-5
y=-4
x=-5
b) Co tam jest przy tej 2 ??
c)
a)
y=6x+26
5x=7y+3
y = 6x+26
5x = 7(6x + 26)+3
y = 6x+26
5x = 42x+182+3
y = 6x+26
5x-42x = 185
y = 6x+26
-37x = 185 / :(-37)
y = 6x+26
x= -5
y = 6*(-5)+26
x = -5
y= -30+26
x = -5
y= -4
x= -5
b)
5x+9y=-2
4x-6y=38
5x+9y=-2
4x=38+6y /:4
5x+9y=-2
x=9,5+1,5y
5(9,5+1,5y)+9y=-2
x=9,5+1,5y
47,5+7,5y+9y=-2
x=9,5+1,5y
16,5y=-49,5 /:16,5
x=9,5+1,5y
y=-3
x=9,5+1,5y
y=-3
x=9,5+1,5*(-3)
y=-3
x=9,5-4,5
y=-3
x=5
c)
5(2x+3) -2(3y-4)=3
3x+0,5-y-1,5=5
10x+15-6y+8=3
3x-y-1=5
10x-6y+23=3
y=3x-1-5
10x-6y+23=3
y=3x-6
10x-6(3x-6)+23=3
y=3x-6
10x-18x+36+23=3
y=3x-6
-8x=3-59
y=3x-6
-8x=-56 /: (-8)
y=3x-6
x=7
y=3x-6
x=7
y=3*7-6
x=7
y=21-6
x=7
y=15
Zadanie 2
a) {2x-4y=7
2x+4y=-7
4x=0
b) { 6x=4y-3
3x+2y=3 /*2
6x+4y=6
6x=-4y+6
12x=-3 /:12
x=-1/4
układ oznaczony
c) {x(6y+3)=3y(2x-5)
x+y=0
6xy+3x=6xy-15y
3x=-15y
x=-5y
y=6x+26
5x=7y+3
y = 6x+26
5x = 7(6x + 26)+3
y = 6x+26
5x = 42x+182+3
y = 6x+26
5x-42x = 185
y = 6x+26
-37x = 185 / :(-37)
y = 6x+26
x= -5
y = 6*(-5)+26
x = -5
y= -30+26
x = -5
y= -4
x= -5
b)
5x+9y=-2
4x-6y=38
5x+9y=-2
4x=38+6y /:4
5x+9y=-2
x=9,5+1,5y
5(9,5+1,5y)+9y=-2
x=9,5+1,5y
47,5+7,5y+9y=-2
x=9,5+1,5y
16,5y=-49,5 /:16,5
x=9,5+1,5y
y=-3
x=9,5+1,5y
y=-3
x=9,5+1,5*(-3)
y=-3
x=9,5-4,5
y=-3
x=5
c)
5(2x+3) -2(3y-4)=3
3x+0,5-y-1,5=5
10x+15-6y+8=3
3x-y-1=5
10x-6y+23=3
y=3x-1-5
10x-6y+23=3
y=3x-6
10x-6(3x-6)+23=3
y=3x-6
10x-18x+36+23=3
y=3x-6
-8x=3-59
y=3x-6
-8x=-56 /: (-8)
y=3x-6
x=7
y=3x-6
x=7
y=3*7-6
x=7
y=21-6
x=7
y=15
Zadanie 2
a) {2x-4y=7
2x+4y=-7
4x=0
b) { 6x=4y-3
3x+2y=3 /*2
6x+4y=6
6x=-4y+6
12x=-3 /:12
x=-1/4
układ oznaczony
c) {x(6y+3)=3y(2x-5)
x+y=0
6xy+3x=6xy-15y
3x=-15y
x=-5y